Investigating Students’ Perspectives on the Use of E-learning MOODLE - Suparjan Suparjan; Nining Ismiyani; Mariyadi Mariyadi; Dian Shintasari; Hery Kresnadi (STAI Hubbulwathan Duri, 2023)
E-Learning has developed rapidly, with many Learning Management Systems (LMS) being used to support learning. The COVID-19 pandemic has provided great opportunities for these developments, one of which is MOODLE LMS which lecturers and students can use to support teaching-learning activities. This study aims to investigate the perspectives of students of the Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, in a state university of West Kalimantan, on the use of the institutional e-learning facilities, namely MOODLE LMS in terms of ease of use and usefulness in the distance learning process amid the Covid-19 pandemic. This study was conducted with qualitative research methods and data collection in the form of semi-structured interviews. This study found that 8 (eight) of the interviewed respondents reported that the MOODLE LMS was very easy to use, especially when logging in, accessing materials, receiving and submitting assignments, and learning about the instructional system when navigating it. MOODLE LMS also allows for quick and on-time assignment submission, provides the convenience of interacting with lecturers, makes learning more interesting and fun, and increases learning motivation. This study is expected to encourage more educators, especially lecturers, to use MOODLE LMS to engage their students in more meaningful learning and complete quality face-to-face interaction in post-pandemic.